Secondary Metabolites from Plants Inhibiting ABC Transporters and Reversing Resistance of Cancer Cells and Microbes to Cytotoxic and Antimicrobial Agents - Wink, Michael (Frontiers in Microbiology, 2012)
Fungal, bacterial and cancer cells can develop resistance against antifungal, antibacterial or anticancer agents. Mechanisms of resistance are complex and often multifactorial. Mechanisms include: 1. Activation of ABC transporters, such as P-gp, which pump out lipophilic compounds that have entered a cell, 2. Activation of cytochrome p450 oxidases which can oxidise lipophilic agents to make them more hydrophilic and accessible for conjugation reaction with glucuronic acid, sulphate or amino acids, and 3. Activation of glutathione transferase, which can conjugate xenobiotics. This review summarises the evidence that secondary metabolites of plants, such as alkaloids, phenolics and terpenoids can interfere with ABC transporters in cancer cells, parasites, bacteria and fungi. Among the active natural products several lipophilic terpenoids ( monoterpenes, diterpenes, triterpenes (including saponins), steroids (including cardiac glycosides) and tetraterpenes) but also some alkaloids (isoquinoline, protoberberine, quinoline, indole, monoterpene indole, and steroidal alkaloids) function probably as competitive inhibitors of P-gp, MRP1 and BCRP in cancer cells, or efflux pumps in bacteria (NorA) and fungi. More polar phenolics (phenolic acids, flavonoids, catechins, chalcones, xanthones, stilbenes, anthocyanins, tannins, anthraquinones, and naphthoquinones) directly inhibit proteins forming several hydrogen and ionic bonds and thus disturbing the 3D structure of the transporters. The natural products may be interesting in medicine or agriculture as they can enhance the activity of active chemotherapeutics or pesticides or even reverse MDR, at least partially, of adapted and resistant cells. If these secondary metabolites are applied in combination with a cytotoxic or antimicrobial agent, they may reverse resistance in a synergistic fashion.